An Investigation of the Dielectric Properties of Barium Oxide: Therm500 Nanofluids at Different Temperatures. (17th August 2022) - Prakash, P.; Catherine Grace John, J.; Kingson Solomon Jeevaraj, A.; Asfaw, Belete Tessema
Abstract : The dielectric characteristics of barium oxide: Therm500 nanofluids were investigated at a static frequency in this study. Barium oxide: Therm500 nanofluids are made by dispersing barium oxide nanoparticles in Therm500 (base fluid) using a sonicator. The static dielectric measurements were made with a frequency domain reflectometry (FDR) sensor. At various temperatures, the values of several dielectric properties, including dipole moment ( μ ), molar polarization ( P ), excess dielectric constant (ε E ), static dielectric constant (ε O ), and excess dipole moment (μ E ), have been measured for BaO: Therm500 nanofluids. Kirkwood factor and Bruggman factor were also computed and presented. The fluctuations in dielectric properties concerning six distinct combinations including 0.001 grams, 0.002 grams, 0.003 grams, 0.004 grams, 0.005 grams, and 0.006 g of nanofluid systems and four different temperatures such as 300 K, 303 K, 313 K, and 323 K are investigated in terms of intermolecular interactions. At all temperatures, the abovementioned dielectric properties BaO: Therm500 nanofluids are positive-negative variations across the whole combination range suggesting in nanofluids the existence of molecular interactions. Synchronization in both parallel and antiparallel of the dipoles in the fluid's mixture are verified by the Kirkwood factor. The Bruggman factor depicts the divergence from the linear relationship in nanofluids, indicating molecular interactions. Dielectric properties of BaO: Therm500 are being studied to understand better their physical, technical, chemical, industrial, laboratory, biological, and pharmaceutical applications.